Non-Enzymatic Electrochemical Glucose Sensors Based on Metal Oxides and Sulfides: Recent Progress and Perspectives - Haibing Zhu; Feng Shi; Maoying Peng; Ye Zhang; Sitian Long; Ruixin Liu; Juan Li; Zhanjun Yang (Chemosensors)
With the sudden advancement of glucose biosensors for monitoring blood glucose levels for the prevention and diagnosis of diabetes, non-enzymatic glucose sensors have aroused great interest owing to their sensitivity, stability, and economy. Recently, researchers have dedicated themselves to developing non-enzymatic electrochemical glucose sensors for the rapid, convenient, and sensitive determination of glucose. However, it is desirable to explore economic and effective nanomaterials with a high non-enzymatic catalysis performance toward glucose to modify electrodes. Metal oxides (MOs) and metal sulfides (MSs) have attracted extensive interest among scholars owing to their excellent catalytic activity, good biocompatibility, low cost, simple synthesis process, and controllable morphology and structure. Nonetheless, the exploitation of MOs and MSs in non-enzymatic electrochemical glucose sensors still suffers from relatively low conductivity and biocompatibility. Therefore, it is of significance to integrate MOs and MSs with metal/carbon/conducive polymers to modify electrodes for compensating the aforementioned deficiency. This review introduces the recent developments in non-enzymatic electrochemical glucose sensors based on MOs and MSs, focusing on their preparation methods and how their structural composition influences sensing performance. Finally, this review discusses the prospects and challenges of non-enzymatic electrochemical glucose sensors.